2022
DOI: 10.4013/ctc.2022.153.01
|View full text |Cite
|
Sign up to set email alerts
|

Construção e evidências de validade baseadas no conteúdo para a Escala de Locus de Controle (ELOCUS)

Abstract: Entende-se por locus de controle a percepção sobre como o indivíduo estabelece o controle de suas ações em busca de um desfecho satisfatório, dividindo-se em interno e externo. Embora o construto tenha uma vasta tradição na pesquisa psicológica e apresente diversas escalas, estas deixaram lacunas como, por exemplo, instabilidade de número de fatores do construto. Neste sentido, foi construída a Escala de Locus de Controle (ELOCUS) que avalia expectativas generalizadas de controle em adultos. O objetivo foi apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Locus of Control Scale (Escala de Locus de Controle, ELOCUS; Couto et al, 2021;2022). This is a self-report instrument with two factors, consisting of 29 items (16 for internal locus of control and 13 for external locus of control), with a Likert-type response format ranging from 1 (has nothing to do with me) to 5 (has everything to do with me).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Locus of Control Scale (Escala de Locus de Controle, ELOCUS; Couto et al, 2021;2022). This is a self-report instrument with two factors, consisting of 29 items (16 for internal locus of control and 13 for external locus of control), with a Likert-type response format ranging from 1 (has nothing to do with me) to 5 (has everything to do with me).…”
Section: Instrumentsmentioning
confidence: 99%
“…However, scales that aim to assess the locus of control without a dependent context (e.g., school, physical health) can be useful for providing comparison and generalization of results. Therefore, seeking to indicate the psychometric qualities of a new locus of control scale for adults (Escala de Locus de Controle, ELOCUS; Couto et al, 2021;2022), this study aimed to verify the associations between locus of control and mental health variables such as depression, anxiety and emotional dysregulation, and their predictive and mediative relationships, as no studies were found in the literature that contemplated models which measured all these variables together.…”
mentioning
confidence: 99%